Factors influencing university students' self-regulation of learning: An exploratory study - Balapumi, R.; von Konsky, Brian; Aitken, A.; McMeekin, David (2016)
Copyright 2016 ACM.University students are expected to self-regulate their learning while maintaining high motivation in their tertiary education. However, not all students possess the competency required to self-regulate their learning independently. Students need guidance and support in developing the skills to self-regulate their learning. The aim of this study was, therefore, to identify factors that influence university students' self-regulation of learning. Structural Equation Modelling (SEM) based Partial Least Square (PLS) analysis revealed that students' goal, employment prospects, self-efficacy, metacognitive knowledge, prior learning experience, peer influence and family influence have a significant effect on university students' self-regulation of learning. Employment opportunities and teaching staff significant were also found to have an indirect impact on students' self-regulation of learning. Based on these results, the role of the teaching staff, academic managers, teaching and learning support staff as well as students themselves are discussed, together with the advancement of future research and practice in the facilitation of self-regulated learning in higher education.